(untitled) - S. Anita, A. Fayaz Ahmed, Y. Sukhi, E. Elakkia (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The transformational reforms in higher education under the National Educational Policy NEP 2020 highlights the policy requirements of holistic, multidisciplinary and futuristic education. It focusses on bringing about the catalyzing of quality research and the possibilities and requirements for the equitable use of technology for better reach in education. The views from educational experts in the NEP conclave which is the starting of series of webinars that are to be conducted to make all the stakeholders and the public informed about the NEP and to get the inputs for effective implementation of the policy are presented in this paper.